Feasibility of Neurorehabilitation Using a Hybrid Assistive Limb for Patients Who Underwent Spine Surgery - Aya Yatsugi; Takashi Morishita; Hiroyuki Fukuda; Naoya Kotani; Kenji Yagi; Hiroshi Abe; Etsuji Shiota; Tooru Inoue (Applied Bionics and Biomechanics)
Recent studies of robotic rehabilitation have demonstrated its efficacy for neurological disorders. However, few studies have used the Hybrid Assistive Limb (HAL) during the early postoperative stage of spine disorders. We aimed to evaluate the safety and efficacy of HAL treatment during the early postoperative period for spine disorder patients. We retrospectively identified patients who underwent spine surgery and who could complete HAL treatment. We evaluated the 10-m walking test (10MWT), the modified Gait Abnormality Rating Scale (GARS-M), Barthel Index (BI), and the walking index for spinal cord injury II (WISCI II) score results before and after robotic rehabilitation. Clinical outcomes were compared after treatment. We included nine patients with various spine problems. After HAL treatment, the speed during the 10MWT significantly improved from 64.1 ± 16.0 to 74.8 ± 10.8 m/min, and the walking cadence decreased from 102.7 ± 17.6 to 92.7 ± 10.9 steps/min. The BI score also improved from 83.3 ± 16.0 to 95.6 ± 5.8, and the WISCI II score improved from 19.7 ± 0.5 to 20.0 ± 0.0. Furthermore, the total GARS-M score improved from 6.0 ± 5.7 to 2.3 ± 3.3. The maximum angles of the trunk swing were improved from 2.2 ± 1.9 to 1.2 ± 0.9 degrees. Neurorehabilitation therapy using HAL for spinal surgery patients was considered feasible following spine surgery.